The Andean Thrust Front Migration and Related Shortening Rates during the Late Pleistocene-Holocene (32° 30′S), Argentina - Victoria Alvarellos; Carlos H. Costa; Lucía Sagripanti; Andrés D. Richard; Lucía Jagoe; Soledad Morales Volosín; Andrés Folguera (Lithosphere, 2025)
At the southern Pampean flat-slab of the Central Andes, Quaternary-active deformation is concentrated at the easternmost thrusts of the Southern Precordillera along the Las Higueras-Las Peñas range (32° 10′-32° 45′S). This range is bounded by the Las Peñas Thrust System (LPTS), which emplaces Cenozoic sedimentary rocks over a suite of Quaternary alluvial deposits under variable shortening rates. This study focuses on the southern part of this range (La Escondida Creek). Here, the east-verging Quaternary-active thrust front has been shifting toward the piedmont area since Pliocene-Pleistocene times, through discrete splays that bound four different morphotectonic domains. To unravel the shortening related to these propagating thrust splays, we applied trishear forward modeling and retrodeformation of geometric markers such as folded and faulted stratigraphic layers and well-preserved alluvial surfaces, supported by detailed topographic surveys. We compare shortening estimations derived from trishear forward models of deformed layers in a propagating thrust exposure with the data obtained from modeling the resulting thrust scarp morphology on an alluvial surface. Shortening rate assessments for the most recent footwall-propagating thrust yielded scattered values; however, the most reliable estimate is likely below 1 mm/a for this Quaternary frontal thrust.